2008
DOI: 10.1007/s10517-009-0316-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgeneration Effects of Antenatal Acute Hypoxia during Early Organogenesis

Abstract: We studied the effect of acute hypobaric hypoxia in early organogenesis on physiological and behavioral parameters of second-generation albino rats. Antenatal acute hypoxia was followed by physical and sexual retardation, increase in the mortality rate, and behavioral changes in second-generation animals (hypoactivity of males and females on day 22 of life and hyperactivity of males on day 57 of life). Second-generation animals exhibited no gender differences in body weight and horizontal and vertical locomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Mammalian studies have shown that prenatal exposure to certain environmental stresses (e.g., hypoxia) and chemical contaminants (e.g., endocrine disrupting chemicals) can lead to alterations in phenotypes (e.g., delayed physical and sexual development, infertility, increased mortality and behavioral changes) in successive generations, despite the offspring have never been directly exposed to the stress and contaminants before [11] , [12] . Such transgenerational effects may not be caused by alterations in DNA sequence but by changes in the epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian studies have shown that prenatal exposure to certain environmental stresses (e.g., hypoxia) and chemical contaminants (e.g., endocrine disrupting chemicals) can lead to alterations in phenotypes (e.g., delayed physical and sexual development, infertility, increased mortality and behavioral changes) in successive generations, despite the offspring have never been directly exposed to the stress and contaminants before [11] , [12] . Such transgenerational effects may not be caused by alterations in DNA sequence but by changes in the epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this, we tested if SP would show a protective action on the behavioral and biochemical changes induced by hypoxia. We used the previously established model, in which acute hypoxia was created in a decompression chamber with female rats sensitized to the insult by pregnancy [21, 24, 31]. Protective action of SP was observed already during the acute hypoxia in decompression chamber.…”
Section: Resultsmentioning
confidence: 99%
“…221 Subsequently, environment hypoxia resulted transgenerational task was detected in rats. 222 Intriguingly, breakthrough finding was reported in fish that hypoxia impairs male reproduction in Oryzias melastigma by declining of spermatozoa quality and quantity, via the methylation regulation. 73,223 Probing the mechanism of hypoxic stress on fish physiology through methylation is being emphasized, including reproductive impairments, 73,223,224 embryogenesis, 225 immunity, 226 growth and development 227 and metabolism.…”
Section: Hypoxic Stressmentioning
confidence: 99%
“…Earlier, the studies reported that exposing monkeys to high altitude with hypoxic stress significantly changed number of spermatozoa and spermatozoa motility 221 . Subsequently, environment hypoxia resulted transgenerational task was detected in rats 222 . Intriguingly, breakthrough finding was reported in fish that hypoxia impairs male reproduction in Oryzias melastigma by declining of spermatozoa quality and quantity, via the methylation regulation 73,223 .…”
Section: Identification Of Dna Methylation Changes In Fish Spermatozo...mentioning
confidence: 99%